2012
DOI: 10.1002/lary.23285
|View full text |Cite
|
Sign up to set email alerts
|

Nasoseptal flap repair after endoscopic transsellar versus expanded endonasal approaches: Is there an increased risk of postoperative cerebrospinal fluid leak?

Abstract: Based on our data, there is no significant increased risk of postoperative CSF leak between transsellar and expanded EEA defects when a PNSF is used. The potential risk of postoperative CSF leaks associated with larger defects created through expanded EEA can be minimized by multilayered closure with a PNSF and meticulous surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 30 publications
1
64
0
4
Order By: Relevance
“…Currently, the incidence of postoperative CSF leaks associated with the use of the nasoseptal flap is approximately 5%, which is comparable to more standard transcranial approaches. 3,7,13,17,18,[22][23][24]28,30,34,37,38 As a result, the PNSF has become the primary workhorse for closure of large skull base defects with high-flow CSF leaks that develop after endoscopic skull base surgery. 39 In our experience with 93 patients requiring PNSF reconstruction of large skull base dural defects after an EEA, we have, to date, been able to achieve an overall rate of postoperative CSF leakage of 3.2%.…”
mentioning
confidence: 99%
“…Currently, the incidence of postoperative CSF leaks associated with the use of the nasoseptal flap is approximately 5%, which is comparable to more standard transcranial approaches. 3,7,13,17,18,[22][23][24]28,30,34,37,38 As a result, the PNSF has become the primary workhorse for closure of large skull base defects with high-flow CSF leaks that develop after endoscopic skull base surgery. 39 In our experience with 93 patients requiring PNSF reconstruction of large skull base dural defects after an EEA, we have, to date, been able to achieve an overall rate of postoperative CSF leakage of 3.2%.…”
mentioning
confidence: 99%
“…We typically do not use tissue sealants or postoperative lumbar drainage for these defects, as this has not made any difference in postoperative CSF leaks. [45][46][47] With the triple-layer repair, we have found that rigid structural reconstruction of the anterior cranial base (with mesh, Medpor, or bone) is not necessary to prevent frontal lobe sagging or encephalocele formation. 48 …”
Section: Skull Base Reconstructionmentioning
confidence: 98%
“…In this setting, the rate of CSF leaks has fallen to 1%-8%, depending on the extent of skull base resection. 8,13,15,17,26,45 There are several reasons why the rate of CSF leak after TEA could be lower than after transsphenoidal surgery. Because the sella turcica is a bony depression within the air-filled sphenoid sinus, grafts used for dural repair are not naturally buttressed in any way.…”
Section: Anticipated Challenges To Teamentioning
confidence: 99%